1998
DOI: 10.1002/(sici)1097-4636(19981205)42:3<368::aid-jbm4>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Long-term bone response to particulate injectable ceramic

Abstract: Biphasic calcium phosphate particles (BCP), alone or combined with a cellulosic ether vehicle in an injectable composite material (COMP), were implanted in femurs of rabbits. The long-term follow-up (up to 78 weeks) indicated: (1) BCP and COMP induced a foreign-body inflammatory reaction but without fibrous encapsulation. Phagocytosis was mediated by mononucleated macrophages (MC) and giant multinucleated cells (GMNC). Phagocytosis was stronger with COMP and required the recruitment of GMNC while it primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…All our in vivo and in vitro experiments with this mixture have demonstrated its biocompatibility and biofunctionality [14][15][16]. Further experiments with IBS in rabbit bone in the same conditions using a new HPMC showed that bone ingrowth occurred faster than in experiments with the first HPMC [13] or with macroporous ceramic blocks [17]. The macromolecular parameters influencing bone growth kinetics are currently unknown and require further investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All our in vivo and in vitro experiments with this mixture have demonstrated its biocompatibility and biofunctionality [14][15][16]. Further experiments with IBS in rabbit bone in the same conditions using a new HPMC showed that bone ingrowth occurred faster than in experiments with the first HPMC [13] or with macroporous ceramic blocks [17]. The macromolecular parameters influencing bone growth kinetics are currently unknown and require further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…6). To analyze these behavioral modifications, changes in chemical degradation and macromolecular conformation were studied by infrared spectroscopy [11][12] showed that "the association of cellulosic ether carrier with bioactive ceramic particules does not detrimentally affect the bony incorporation of BCP particles" [13]. All our in vivo and in vitro experiments with this mixture have demonstrated its biocompatibility and biofunctionality [14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…A v ariety of injectable materials, both ceramic-and polymer-based, have been developed for use in multiple orthopaedic applications [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The combination of ceramic particles with polymeric matrices has also been extensiv ely inv estigated, in an attempt to mimic bone tissue, which may itself be seen as a complex composite material made of organic and inorganic components.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of ceramic particles with polymeric matrices has also been extensiv ely inv estigated, in an attempt to mimic bone tissue, which may itself be seen as a complex composite material made of organic and inorganic components. Different ceramic phases have been used, hydroxyapatite and tricalcium phosphate being the most common [4][5][6][7][8][9], as well as several polymeric matrices, both from synthetic [10][11][12][13][14] or natural origin, the latter including collagen, chitosan, gelatine and alginate, among others [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical handling properties of them are limited 45 . Bone cements have been shown to conduct bone growth, but will also induce foreign-body cell reactions 46 . Poor mechanical strength and insufficient adhesion between the bone and the cement as well as low degradation rate restricting the use of some bone filler materials 47,48 .…”
Section: Discussionmentioning
confidence: 99%